Preparation method of pre-sodium-modified sodium ion battery positive electrode sodium ferric sulfate material

Through the preparation method of pre-sodium sodium ferrosulfate material, the problem of insufficient structural stability and electrochemical performance of the positive electrode material of sodium ion battery is solved, and high energy density and low cost effects are achieved.

CN119503890APending Publication Date: 2025-02-25ZIGONG JIA SODIUM NEW MATERIALS TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411685673.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-23
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In existing sodium ion batteries, the structural stability and electrochemical performance of the positive electrode material are insufficient, resulting in limited energy density improvement, and at the same time, the cost is high, making it difficult to meet the requirements of mass production.

Method used

The preparation method of pre-sodium iron sulfate material is adopted. By wet mixing iron, sulfur, sodium, antioxidant and inorganic carbon source, a raw material solution is formed, and then calcined at high temperature to form a high crystalline Na2+2xFe2-x(SO4)3/C material, and amorphously coated sodium supplement compound on the surface of the material to improve the structural stability and electrochemical properties of the material.

Benefits of technology

The structural stability and electrochemical performance of the pre-sodium sodium ion battery positive electrode material has been improved, with low cost, high charging capacity and significantly improved energy density.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a pre-sodium-modified sodium ion battery positive electrode sodium ferric sulfate material. The preparation method comprises the following steps: S1, mixing raw material solutions: mixing an iron source, a sulfur source, a sodium source, an antioxidant and an inorganic carbon source by a wet method to form the raw material solutions; s2, preparation of precursor powder: drying and carrying out solid-liquid separation to obtain the precursor powder; s3, performing high-temperature calcination: performing calcination in a protective atmosphere to form a high-crystalline-state Na < 2 + 2x > Fe < 2-x > (SO4) < 3 > / C material; s4, mixing precursor slurry: dissolving a sodium supplementing compound in an organic reagent, and then adding a high crystalline state Na < 2 + 2 > x Fe < 2-x > (SO4) 3 / C material to form the precursor slurry; s5, drying and separating: drying the precursor slurry to obtain a pre-sodium-modified Na < 2 + 2x > Fe < 2-x > (SO4) 3 / C composite material; in Na < 2 + 2x > Fe < 2-x > (SO4) 3, x < 0.5 > is greater than or equal to 0. The preparation method of the pre-sodium-modified sodium ion battery positive electrode sodium ferric sulfate material has the characteristics of high structural stability, excellent electrochemical performance and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a pre-sodiumized sodium ferric sulfate positive electrode material for a sodium ion battery. Background Art

[0002] The performance of cathode materials has a significant impact on the energy density and electrochemical performance of sodium-ion battery systems. Sodium-ion battery materials that are truly suitable for mass production need to meet the characteristics of low cost, high performance, and easy processing. However, the layered oxides, Prussian blue systems, and polyanion materials currently available on the market have different performances, and there are few materials with excellent comprehensive performance.

[0003] Sulfate materials are a branch of positive electrode materials for polyanion sodium-ion batteries. They are rich in resources, simple in preparation process, high in voltage platform, and high in system energy density. The market currently positions them in the low-end power field. However, sulfate materials are mainly composed of a three-dimensional framework structure consisting of Na-O polyhedrons, Fe-O polyhedrons, and SO polyhedrons connected to each other in the form of common points / edges. The structure contains abundant sodium storage sites, and when the Fe ions in the structure undergo redox reaction, the sodium ions can undergo complete deintercalation reaction, resulting in the material's first-week coulomb efficiency approaching 100%.

[0004] At present, the first-week efficiency of hard carbon negative electrode materials used in sodium-ion batteries is only 90%. When it is combined with sodium iron sulfate positive electrode to form a full battery, it will consume about 10% of the sodium ions on the positive electrode side, resulting in a significant reduction in the reversible capacity of the positive electrode side, affecting the improvement of the battery's energy density. Summary of the invention

[0005] The invention aims to provide a method for preparing a pre-sodiumized sodium ferric sulfate positive electrode material for a sodium ion battery, which has the characteristics of high structural stability, excellent electrochemical performance and low cost.

[0006] The present invention can be implemented by the following technical solutions: The invention discloses a method for preparing a pre-sodiumized sodium ferric sulfate positive electrode material for a sodium ion battery, comprising the following steps: S1. Mixing of raw material solutions: mixing and dissolving the iron source, sulfur source, sodium source, antioxidant, and inorganic carbon source by wet method to form a raw material solution; S2. Preparation of precursor powder: drying the raw material solution to achieve solid-liquid separation to obtain dry precursor powder; S3, high temperature calcination: calcine the above precursor powder in a protective atmosphere to form a highly crystalline Na 2+2x Fe 2-x (SO4)3 / C materials; S4, Precursor slurry mixing: Dissolve the sodium supplement compound in the organic reagent and add the highly crystalline Na2+2x Fe 2-x (SO4)3 / C material, forming a precursor slurry; S5, drying and separation: drying the precursor slurry to remove the organic reagent to obtain the pre-sodiumized Na 2+2x Fe 2-x (SO4)3 / C composites; In Na 2+2x Fe 2-x In (SO4)3, 0≤x0.5.

[0007] In the present invention, the pre-sodiumization of sulfate materials can be achieved by compounding easily decomposable sodium salts with materials. First, a sodium iron sulfate material is prepared, and then it is mixed with a pre-sodiumization salt reagent in an organic solvent, so that the pre-sodiumization salt reagent is dissolved in the organic solvent, and then the salt is spray-dried to achieve amorphous disordered coating on the surface of the sodium iron sulfate material, and the characteristic of the salt compound decomposing under high pressure is utilized to achieve its supplementation of sodium ions on the hard carbon negative electrode side, thereby improving the energy density of the sodium ion battery. The material prepared by this process has a high charging capacity and excellent electrochemical performance.

[0008] Furthermore, in step S4, the amount of sodium supplementing compound added is 1.5~5wt% of the weight of the sodium ferric sulfate material; when the amount of sodium supplementing compound added is less than 1.5wt%, it is not enough to compensate for the consumption of sodium ions on the negative electrode side, and when the amount of sodium supplementing compound added is higher than 5wt%, the excess compound is not easily dissolved in the organic reagent, and the excess compound will also increase the production cost.

[0009] Furthermore, in step S4, the sodium supplement compound is one or more of sodium oxalate, sodium carbonate, sodium bicarbonate, sodium oxide, and sodium peroxide; its characteristic is that this type of substance is easy to dissociate sodium ions under high pressure conditions in the battery to supplement the consumption of sodium ions on the negative electrode side.

[0010] Furthermore, in step S4, the organic reagent is one or more of volatile organic reagents such as ethanol, acetone, acetonitrile, ether, benzene, etc.; its purpose is to dissolve the sodium supplement compound so that it can be adsorbed on the surface of the sodium ferric sulfate material in atomic form as much as possible.

[0011] Further, in step S3, the calcination temperature is 320-430°C and the time is >0.01H, the purpose of which is to volatilize and remove the easily decomposable components in the sodium source, iron source, sulfur source and antioxidant, and promote the Na 2+2x Fe 2-xThe elements in the (SO4)3 structure bond with each other to form a highly crystalline material; when the temperature is lower than 320°C, the sulfate material cannot fully melt and crystallize, affecting the subsequent material properties, and when the temperature is higher than 430°C, the sulfate material will decompose into iron oxide and sulfur oxide gas.

[0012] Furthermore, in steps S2 and S5, the drying method is one or more of flash drying, spray drying, vacuum drying, freeze drying, and air drying.

[0013] Furthermore, in step S3, the protective atmosphere is one or more of nitrogen, argon, nitrogen-hydrogen, and argon-hydrogen.

[0014] Furthermore, in step S1, the antioxidant is one or more of ascorbic acid and its derivatives, phytic acid and its derivatives, butylated hydroxymethoxybenzene, tert-butylhydroquinone, butylated hydroxytoluene, and ethoxyquinoline; the purpose is to prevent the oxidation of divalent iron ions in the solution.

[0015] Furthermore, in step S1, the inorganic carbon is one or more of carbon black and its derivatives, graphene and its derivatives, carbon nanotubes and its derivatives, carbon fibers and their derivatives; the purpose is to construct an electronic conductive network in the sodium iron sulfate material and reduce the internal resistance of the material.

[0016] Further, in step S1, the iron source is one or more of ferrous sulfate, ferric sulfate, iron powder, ferrous oxide, ferric oxide, ferric hydroxide, ferric oxide, ferric acetate; the sulfur source is one or more of sulfuric acid, ferrous sulfate, ammonium sulfate, and sodium sulfate; the sodium source is one or more of sodium formate, sodium acetate, sodium sulfate, sodium nitrate, sodium hydroxide, sodium carbonate, and sodium bicarbonate.

[0017] The present invention provides a method for preparing a sodium ferric sulfate material for a positive electrode of a sodium ion battery, which has the following beneficial effects: First, the structural stability is high. The sintering temperature of sodium iron sulfate materials is generally lower than 450°C, and the bonding energy of the elements in the structure is generally low. When the material is in a water-containing environment, the sulfate ions on the surface will spontaneously combine with water, and the hydrogen ions generated by the reaction will be embedded in the material and exchange with the sodium ions in the structure, causing the material to be deactivated and affecting the electrochemical properties of the material. The sodium-supplementing compound exists in an amorphous and disordered state on the interface of the material, which will reduce the direct contact between the sulfate ions on the interface of the material and water to a certain extent, which is conducive to improving the interface stability of the material.

[0018] Second, excellent electrochemical performance, pre-sodiumization Na 2+2x Fe 2-xIn the (SO4)3 / C composite material, the sodium-supplementing compound is attached to the surface of the sodium iron sulfate material in an amorphous disordered state, and the bonding energy between its elements is low and the activation energy barrier is low. When the battery voltage is charged to above 4.3V, the sodium-supplementing compound is activated under overvoltage, decomposing sodium ions and a small amount of gas, and the free sodium ions are supplemented to the negative electrode side, thereby filling the problem of low first efficiency of the negative electrode. Ultimately, the battery exhibits a higher reversible capacity, corresponding to a higher energy density of the battery.

[0019] Third, the cost is low. In the present invention, the sodium supplementation compound is a common inorganic sodium salt, which has a large market scale and low cost. In addition, the present invention uses a simple physical mixing of sodium ferric sulfate and the sodium supplementation compound, and uses a small amount of inorganic sodium salt to dissolve in an organic solvent to form a uniform ionic saturated solution, and then adds the sodium ferric sulfate material, so that the sodium supplementation compound is uniformly attached to the surface of the sodium ferric sulfate material after drying. This method is different from traditional chemical pre-sodiumization or metallic sodium, etc. The latter has strict requirements on the oxygen content and water content in the environment, and special equipment and special processes are required to achieve it, and the production investment cost is relatively large. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0021] The invention discloses a method for preparing a pre-sodiumized sodium ferric sulfate positive electrode material for a sodium ion battery, comprising the following steps: S1. Mixing of raw material solutions: mixing and dissolving the iron source, sulfur source, sodium source, antioxidant, and inorganic carbon source by wet method to form a raw material solution; S2. Preparation of precursor powder: drying the raw material solution to achieve solid-liquid separation to obtain dry precursor powder; S3, high temperature calcination: calcine the above precursor powder in a protective atmosphere to form a highly crystalline Na 2+2x Fe 2-x (SO4)3 / C materials; S4, Precursor slurry mixing: Dissolve the sodium supplement compound in the organic reagent and add the highly crystalline Na 2+2x Fe 2-x (SO4)3 / C material, forming a precursor slurry; S5, drying and separation: drying the precursor slurry to remove the organic reagent to obtain the pre-sodiumized Na 2+2x Fe 2-x (SO4)3 / C composites; In Na 2+2x Fe 2-x In (SO4)3, 0≤x0.5.

[0022] Furthermore, in step S4, the amount of sodium supplementing compound added is 1.5-5wt% of the weight of the sodium ferric sulfate material.

[0023] Furthermore, in step S4, the sodium supplement compound is one or more of sodium oxalate, sodium carbonate, sodium bicarbonate, sodium oxide, and sodium peroxide.

[0024] Furthermore, in step S4, the organic reagent is one or more of ethanol, acetone, acetonitrile, ether, and benzene.

[0025] Further, in step S3, the calcination temperature is 320-430°C, and the time is >0.01H.

[0026] Furthermore, in steps S2 and S5, the drying method is one or more of flash drying, spray drying, vacuum drying, freeze drying, and air drying.

[0027] Furthermore, in step S3, the protective atmosphere is one or more of nitrogen, argon, nitrogen-hydrogen, and argon-hydrogen.

[0028] Furthermore, in step S1, the antioxidant is one or more of ascorbic acid and its derivatives, phytic acid and its derivatives, butylated hydroxymethoxybenzene, tert-butylhydroquinone, butylated hydroxytoluene, and ethoxyquinoline.

[0029] Furthermore, in step S1, the inorganic carbon is one or more of carbon black and its derivatives, graphene and its derivatives, carbon nanotubes and its derivatives, carbon fibers and their derivatives.

[0030] Further, in step S1, the iron source is one or more of ferrous sulfate, ferric sulfate, iron powder, ferrous oxide, ferric oxide, ferric hydroxide, ferric oxide, ferric acetate; the sulfur source is one or more of sulfuric acid, ferrous sulfate, ammonium sulfate, and sodium sulfate; the sodium source is one or more of sodium formate, sodium acetate, sodium sulfate, sodium nitrate, sodium hydroxide, sodium carbonate, and sodium bicarbonate.

[0031] Example 1 This embodiment relates to a method for preparing a pre-sodiumized sodium ferric sulfate positive electrode material for a sodium ion battery, comprising the following steps: S1. Mixing of raw material solutions: Wet-mix and dissolve an iron source, a sulfur source, a sodium source, an antioxidant, and an inorganic carbon source to form a raw material solution. Specifically, the antioxidant is ascorbic acid and its derivatives; the inorganic carbon is carbon black and its derivatives, graphene and its derivatives; the iron source and the sulfur source are both ferrous sulfate and ferric sulfate; the sodium source is sodium formate, sodium acetate, sodium sulfate, and sodium nitrate.

[0032] S2. Preparation of precursor powder: drying the raw material solution to achieve solid-liquid separation and obtain dry precursor powder. Specifically, the drying method is flash drying or spray drying.

[0033] S3, high temperature calcination: calcine the above precursor powder in a protective atmosphere to form a highly crystalline Na 2+2x Fe 2-x (SO4)3 / C material. Specifically, the calcination temperature is 430°C, the time is 3H, and the protective atmosphere is nitrogen.

[0034] S4, Precursor slurry mixing: Dissolve the sodium supplement compound in the organic reagent and add the highly crystalline Na 2+2x Fe 2-x (SO4)3 / C material is used to form a precursor slurry. Specifically, the amount of sodium supplementing compound added is 1.5wt% of the weight of the sodium iron sulfate material; the sodium supplementing compound is sodium oxalate or sodium carbonate; and the organic reagent is ethanol or acetone.

[0035] S5, drying and separation: drying the precursor slurry to remove the organic reagent to obtain the pre-sodiumized Na 2+2x Fe 2-x (SO4)3 / C composite materials; in Na 2+2x Fe 2-x In (SO4)3, 0≤x0.5. Specifically, the drying method is flash drying, spray drying, or vacuum drying.

[0036] Example 2 This embodiment relates to a method for preparing a pre-sodiumized sodium ferric sulfate positive electrode material for a sodium ion battery, comprising the following steps: S1. Mixing of raw material solutions: Wet-mix and dissolve an iron source, a sulfur source, a sodium source, an antioxidant, and an inorganic carbon source to form a raw material solution. Specifically, the antioxidant is phytic acid and its derivatives, butylated hydroxymethoxybenzene, and tert-butylhydroquinone; the inorganic carbon is carbon nanotubes and their derivatives, and carbon fibers and their derivatives; the iron source is ferrous oxide, ferric oxide, ferric hydroxide, and ferric oxyhydroxide; the sulfur source is ammonium sulfate and sodium sulfate; and the sodium source is sodium nitrate, sodium hydroxide, and sodium carbonate.

[0037] S2. Preparation of precursor powder: Dry the raw material solution to achieve solid-liquid separation and obtain dry precursor powder. Specifically, the drying method is spray drying.

[0038] S3, high temperature calcination: calcine the above precursor powder in a protective atmosphere to form a highly crystalline Na 2+2x Fe 2-x (SO4)3 / C material. Specifically, the calcination temperature is 360°C, the time is 1H, and the protective atmosphere is nitrogen-hydrogen or argon-hydrogen.

[0039] S4, Precursor slurry mixing: Dissolve the sodium supplement compound in the organic reagent and add the highly crystalline Na 2+2x Fe 2-x (SO4)3 / C material is used to form a precursor slurry. Specifically, the amount of sodium supplementing compound added is 5wt% of the weight of the sodium iron sulfate material; the sodium supplementing compound is sodium oxide or sodium peroxide; and the organic reagent is acetonitrile, ether, or benzene.

[0040] S5, drying and separation: drying the precursor slurry to remove the organic reagent to obtain the pre-sodiumized Na 2+2x Fe 2-x (SO4)3 / C composite materials; in Na 2+2x Fe 2-x In (SO4)3, 0≤x0.5. Specifically, the drying method is forced air drying.

[0041] Example 3 This embodiment relates to a method for preparing a pre-sodiumized sodium ferric sulfate positive electrode material for a sodium ion battery, comprising the following steps: S1. Mixing of raw material solutions: Wet-mix and dissolve an iron source, a sulfur source, a sodium source, an antioxidant, and an inorganic carbon source to form a raw material solution. Specifically, the antioxidant is butylated hydroxymethoxybenzene, tert-butylhydroquinone, butylated hydroxytoluene, and ethoxyquinoline; the inorganic carbon is carbon black and its derivatives, graphene and its derivatives; the iron source is ferroferric oxide and ferrous acetate; the sulfur source is sulfuric acid, sodium sulfate; and the sodium source is sodium formate, sodium carbonate, and sodium bicarbonate.

[0042] S2. Preparation of precursor powder: Dry the raw material solution to achieve solid-liquid separation and obtain dry precursor powder. Specifically, the drying method is vacuum drying or freeze drying.

[0043] S3, high temperature calcination: calcine the above precursor powder in a protective atmosphere to form a highly crystalline Na 2+2x Fe 2-x (SO4)3 / C material. Specifically, the calcination temperature is 320°C, the time is 4 hours, and the protective atmosphere is nitrogen or argon.

[0044] S4, Precursor slurry mixing: Dissolve the sodium supplement compound in the organic reagent and add the highly crystalline Na 2+2x Fe 2-x (SO4)3 / C material is used to form a precursor slurry. Specifically, the amount of sodium supplementing compound added is 3wt% of the weight of the sodium iron sulfate material; the sodium supplementing compound is sodium oxalate or sodium carbonate; and the organic reagent is ethanol, ether or benzene.

[0045] S5, drying and separation: drying the precursor slurry to remove the organic reagent to obtain the pre-sodiumized Na 2+2x Fe 2-x(SO4)3 / C composite materials; in Na 2+2x Fe 2-x In (SO4)3, 0≤x0.5. Specifically, the drying method is spray drying.

[0046] Example 4 This embodiment relates to a method for preparing a pre-sodiumized sodium ferric sulfate positive electrode material for a sodium ion battery, comprising the following steps: S1. Mixing of raw material solutions: Wet-mix and dissolve an iron source, a sulfur source, a sodium source, an antioxidant, and an inorganic carbon source to form a raw material solution. Specifically, the antioxidant is hydroxytoluene and ethoxyquinoline; the inorganic carbon is carbon black and its derivatives, carbon fiber and its derivatives; the iron source is ferrous sulfate, ferric hydroxide, ferric oxyhydroxide, ferric oxide, and ferric acetate; the sulfur source is sulfuric acid and sodium sulfate; and the sodium source is sodium formate and sodium acetate.

[0047] S2. Preparation of precursor powder: Dry the raw material solution to achieve solid-liquid separation and obtain dry precursor powder. Specifically, the drying method is spray drying or blast drying.

[0048] S3, high temperature calcination: calcine the above precursor powder in a protective atmosphere to form a highly crystalline Na 2+2x Fe 2-x (SO4)3 / C material. Specifically, the calcination temperature is 400°C, the time is 2H, and the protective atmosphere is nitrogen or argon.

[0049] S4, Precursor slurry mixing: Dissolve the sodium supplement compound in the organic reagent and add the highly crystalline Na 2+2x Fe 2-x (SO4)3 / C material is used to form a precursor slurry. Specifically, the amount of sodium supplementing compound added is 2wt% of the weight of the sodium iron sulfate material; the sodium supplementing compound is sodium oxalate, sodium carbonate, sodium bicarbonate; and the organic reagent is ethanol and acetone.

[0050] S5, drying and separation: drying the precursor slurry to remove the organic reagent to obtain the pre-sodiumized Na 2+2x Fe 2-x (SO4)3 / C composite materials; in Na 2+2x Fe 2-x In (SO4)3, 0≤x0.5. Specifically, the drying method is spray drying.

[0051] Example 5 This embodiment relates to a method for preparing a pre-sodiumized sodium ferric sulfate positive electrode material for a sodium ion battery, comprising the following steps: S1. Mixing of raw material solutions: Wet-mix and dissolve an iron source, a sulfur source, a sodium source, an antioxidant, and an inorganic carbon source to form a raw material solution. Specifically, the antioxidant is ascorbic acid and its derivatives, phytic acid and its derivatives, butylated hydroxymethoxybenzene, etc.; the inorganic carbon is carbon black and its derivatives, carbon fiber and its derivatives; the iron source is ferrous sulfate, ferric sulfate, iron powder, ferrous oxide; the sulfur source is sulfuric acid, ferrous sulfate, ammonium sulfate; the sodium source is sodium formate, sodium acetate, sodium sulfate, sodium nitrate.

[0052] S2. Preparation of precursor powder: drying the raw material solution to achieve solid-liquid separation and obtain dry precursor powder. Specifically, the drying method is flash drying or spray drying.

[0053] S3, high temperature calcination: calcine the above precursor powder in a protective atmosphere to form a highly crystalline Na 2+2x Fe 2-x (SO4)3 / C material. Specifically, the calcination temperature is 3500°C, the time is 3H, and the protective atmosphere is nitrogen or argon.

[0054] S4, Precursor slurry mixing: Dissolve the sodium supplement compound in the organic reagent and add the highly crystalline Na 2+2x Fe 2-x (SO4)3 / C material is used to form a precursor slurry. Specifically, the amount of sodium supplementing compound added is 4wt% of the weight of the sodium iron sulfate material; the sodium supplementing compound is sodium bicarbonate, sodium oxide, sodium peroxide; and the organic reagent is ethanol and acetone.

[0055] S5, drying and separation: drying the precursor slurry to remove the organic reagent to obtain the pre-sodiumized Na 2+2x Fe 2-x (SO4)3 / C composite materials; in Na 2+2x Fe 2-x In (SO4)3, 0≤x0.5. Specifically, the drying method is flash drying or spray drying.

[0056] Application Example 1 Na 2.4 Fe 1.8 Synthesis and electrochemical performance of (SO4)3 / CNT / sodium oxalate composites This embodiment involves Na 2.4 Fe 1.8 The (SO4)3 / CNT / sodium oxalate composite material, the preparation method thereof comprises the following steps: Step 1: Dissolve atomized elemental iron powder, sodium formate, and sulfuric acid in water at a molar ratio of 1.8:2.4:3, and add a small amount of ascorbic acid (the added amount is 0.01 times the molar amount of elemental iron powder) and CNT slurry (5wt% solid content, the added amount is 6wt% of the total solid content in the solution) to the above solution to form a uniform solution; Step 2: spray drying the above solution, with the air inlet temperature of 200°C and the air outlet temperature of 80°C, to achieve solid-liquid separation and obtain a dry precursor powder; Step 3: In a nitrogen atmosphere, the precursor powder is calcined at 360°C for 5 hours, and the highly crystalline Na 2。4 Fe 1.8 (SO4)3 / CNT materials; Step 4: Sodium oxalate (added in an amount of Na 2.4 Fe 1.8 (SO4)3 / 2.5wt% of the CNT material weight) was dissolved in ethanol solvent, and then the highly crystalline Na 2.4 Fe 1.8 (SO4)3 / C material is added to the above ethanol solution to form a uniform precursor slurry; Step 5: Dry the precursor slurry using a blower dryer at 80°C until the ethanol reagent is completely evaporated to obtain Na 2.4 Fe 1.8 (SO4)3 / CNT / sodium oxalate composite material.

[0057] The results in Table 1 show that the specific surface area of ​​the material is 5.6 m 2 / g, compared with the material without interface sodium supplementation compound modification in Comparative Example 1, its specific surface area is significantly reduced, indicating that the sodium supplementation compound is attached to the Na in an amorphous and disordered form. 2.4 Fe 1.8 The surface of (SO4)3 / CNT material plays a role of filling holes to a certain extent, the interface densification degree increases, and the specific surface area decreases, which has a significant improvement on the storage of materials in humid air. The results in Table 1 show that Na 2.4 Fe 1.8 After the (SO4)3 / CNT / sodium oxalate composite material was exposed to a 50% humid environment for one week, XRD refinement analysis showed that its phase purity was as high as 98.4%, and the hydrated phase accounted for only 1.6%, indicating that the material has excellent air stability. This is related to the coating of sodium oxalate on the surface of the material in an amorphous and disordered form. Its relatively dense coating blocks the side reaction of moisture and the material interface to a certain extent, thereby improving the air stability of the material.

[0058] Will Na 2.4 Fe 1.8(SO4)3 / CNT / sodium oxalate composite material, AB, and PVDF were mixed and slurried in a mass ratio of 9.2:0.4:0.4. After grinding, the black slurry was coated on aluminum foil using a 150um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, with metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and the separator was a PP / PE / PP three-layer separator, and assembled into a CR2016 button battery in a glove box.

[0059] The button cell was subjected to constant current charge and discharge tests at a current density of 0.1C (1C = 120mAh / g). The results in Table 1 show that within the voltage range of 2.0-4.5V, the first week charge capacity of the electrode is 126.3mAh / g, which is significantly higher than that of Comparative Example 1. The reason is that Na 2.4 Fe 1.8 The amorphous disordered sodium oxalate on the surface of the (SO4)3 / CNT / sodium oxalate composite material gradually decomposes above 4.3V, releasing a large amount of sodium ions, thereby increasing the first-cycle charge capacity of the material. 2.4 Fe 1.8 The first cycle coulombic efficiency of (SO4)3 / CNT material decreased from 98.5% (Comparative Example 1) to 89.2%. 2.4 Fe 1.8 The (SO4)3 / CNT / sodium oxalate composite material was assembled with biomass hard carbon into a full battery system and its performance was tested. The results showed that at a rate of 0.1C, the Na 2.4 Fe 1.8 The effective reversible capacity of the (SO4)3 / CNT / sodium oxalate composite material is 110.3 mAh / g, which is significantly better than that of Comparative Example 1, indicating that the decomposition of sodium oxalate on the positive electrode side of the battery can compensate for the consumption of sodium ions on the negative electrode side due to the low first efficiency, thereby making Na 2.4 Fe 1.8 The utilization rate of sodium storage sites in the (SO4)3 material structure is close to 100%, which effectively improves the energy density of the battery system.

[0060] Application Example 2 Na 2.4 Fe 1.8 Synthesis and electrochemical properties of (SO4)3 / CNT / sodium carbonate composites This embodiment involves Na 2.4 Fe 1.8 The (SO4)3 / CNT / sodium carbonate composite material, the preparation method thereof comprises the following steps: Step 1: Dissolve atomized elemental iron powder, sodium formate, and sulfuric acid in water at a molar ratio of 1.8:2.4:3, and add a small amount of ascorbic acid (the added amount is 0.01 times the molar amount of elemental iron powder) and CNT slurry (5wt% solid content, the added amount is 6wt% of the total solid content in the solution) to the above solution to form a uniform solution; Step 2: spray drying the above solution, with the air inlet temperature of 200°C and the air outlet temperature of 80°C, to achieve solid-liquid separation and obtain a dry precursor powder; Step 3: In a nitrogen atmosphere, the precursor powder is calcined at 360°C for 5 hours, and the highly crystalline Na 2.4 Fe 1.8 (SO4)3 / CNT materials; Step 4: Sodium carbonate (added in an amount of Na 2.4 Fe 1.8 (SO4)3 / 1.98wt% of the CNT material weight) was dissolved in acetone solvent, and then the highly crystalline Na 2.4 Fe 1.8 (SO4)3 / C material is added to the above acetone solution to form a uniform precursor slurry; Step 5: Dry the precursor slurry with a blast dryer at 80°C until the acetone reagent is completely volatilized to obtain Na 2.4 Fe 1.8 (SO4)3 / CNT / sodium oxalate composite material.

[0061] The results in Table 1 show that the specific surface area of ​​the material is 6.2 m 2 / g, which is lower than that of the material in Comparative Example 1, indicating that after the material interface is modified by amorphous disordered sodium carbonate, its interface pores are filled to a certain extent and the specific surface area is significantly reduced. The results in Table 1 show that Na 2.4 Fe 1.8 After the (SO4)3 / CNT / sodium carbonate composite material was exposed to a 50% humid environment for one week, XRD refinement analysis showed that its phase purity was as high as 98.6%, and the hydrated phase accounted for only 1.4%, which showed excellent air stability compared with the material without any inorganic coating in Comparative Example 1. This shows that the amorphous and disordered sodium carbonate coating layer at the interface of the material has hindered the direct contact between moisture and the interior of the material to a certain extent, reducing the escape of sodium ions in the structure and the transformation of the hydrated phase, thereby improving the air stability of the material.

[0062] Will Na 2.4 Fe 1.8(SO4)3 / CNT / sodium carbonate composite material, AB, and PVDF were mixed and slurried in a mass ratio of 9.2:0.4:0.4. After being ground evenly, the black slurry was coated on aluminum foil using a 150um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, with metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer diaphragm as the separator, and assembled into a CR2016 button cell in a glove box.

[0063] The button cell was subjected to constant current charge and discharge tests at a current density of 0.1C (1C=120mAh / g). The results in Table 1 show that within the voltage range of 2.0-4.5V, the first-cycle charge capacity of the electrode is 124.6mAh / g, which is significantly higher than that of Comparative Example 1. The reason for this is that the amorphous disordered sodium carbonate on the surface of the composite material decomposes in large quantities under high voltage to release more sodium ions, which increases the first-cycle charge capacity of the material and reduces the first-cycle coulomb efficiency of the material. Here, we further calculate the Na 2.4 Fe 1.8 The (SO4)3 / CNT / sodium carbonate composite material was assembled with biomass hard carbon into a full battery system and its performance was tested. The results showed that at a rate of 0.1C, the Na 2.4 Fe 1.8 The effective reversible capacity of the (SO4)3 / CNT / sodium carbonate composite material is 110.2 mAh / g, which is significantly better than that of Comparative Example 1. This indicates that the sodium ions released by the decomposition of inorganic salts under high pressure on the positive electrode side can make up for the irreversible consumption of sodium ions on the negative electrode side, thereby ensuring that all sodium ions in the positive electrode structure can undergo a completely reversible deintercalation reaction, thereby improving the capacity and energy density of the entire battery system.

[0064] Comparative Example 1 Na 2.4 Fe 1.8 Synthesis and electrochemical properties of (SO4)3 / CNT materials This embodiment involves Na 2.4 Fe 1.8 The (SO4)3 / CNT composite material, the preparation method thereof comprises the following steps: Step 1: Dissolve atomized elemental iron powder, sodium formate, and sulfuric acid in water at a molar ratio of 1.8:2.4:3, and add a small amount of ascorbic acid (the added amount is 0.01 times the molar amount of elemental iron powder) and CNT slurry (5wt% solid content, the added amount is 6wt% of the total solid content in the solution) to the above solution to form a uniform solution; Step 2: spray drying the above solution, with the air inlet temperature of 200°C and the air outlet temperature of 80°C, to achieve solid-liquid separation and obtain a dry precursor powder; Step 3: In a nitrogen atmosphere, the precursor powder is calcined at 360°C for 5 hours, and the highly crystalline Na 2+2x Fe 2-x (SO4)3 / CNT materials.

[0065] The results in Table 1 show that the specific surface area of ​​the material is 11.4 m 2 / g, compared with the materials modified with sodium supplementing compounds in Examples 1 and 2, its specific surface area is larger, indicating that the material has more pores on the surface, the degree of densification is smaller, and the probability of reaction increases after contact with humid air. The results in Table 1 show that Na 2.4 Fe 1.8 After the (SO4)3 / CNT material was exposed to a 50% humid environment for one week, XRD refinement analysis showed that its phase purity was only 78.3%, and the hydrated phase accounted for as high as 21.7%, indicating that the material has poor air stability. This is related to the fact that the larger specific surface area of ​​the material increases its hygroscopicity in humid air, causing the interface structure of the material to be reorganized, and excess water is embedded in the bulk phase of the material, causing the material to reorganize and form new compounds.

[0066] Will Na 2.4 Fe 1.8 (SO4)3 / CNT material, AB, and PVDF were mixed and slurried in a mass ratio of 9.2:0.4:0.4. After grinding, the black slurry was coated on aluminum foil using a 150um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, with metallic sodium as the counter electrode, 1mol / LNaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer diaphragm as the separator, and assembled into a CR2016 button cell in a glove box.

[0067] The button cell was subjected to constant current charge and discharge tests at a current density of 0.1C (1C=120mAh / g). The results in Table 1 show that within the voltage range of 2.0-4.5V, the first week charge capacity of the electrode is 113.5mAh / g, which is significantly lower than that of Application Examples 1 and 2, indirectly proving that the sodium-supplementing compounds attached to the surface of the sodium ferric sulfate material can decompose to a certain extent and provide sodium ions. Here, we further convert Na 2.4 Fe 1.8 The (SO4)3 / CNT composite material and biomass hard carbon were assembled into a full battery system and its performance was tested. The results showed that at a rate of 0.1C, the Na 2.4 Fe1.8 The effective reversible specific capacity of (SO4)3 / CNT material is only 101.1 mAh / g, which is about 10% lower than that of Application Examples 1 and 2, indicating that part of the sodium ions are consumed by the negative electrode side, resulting in a significant reduction in the sodium ions that can be reversibly embedded back into the positive electrode side, ultimately leading to a decrease in battery capacity and energy density.

[0068] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.

Claims

1. A method for preparing a pre-sodiumized sodium ferric sulfate positive electrode material for a sodium ion battery, characterized in that The following steps are involved: S1. Mixing of raw material solutions: mixing and dissolving the iron source, sulfur source, sodium source, antioxidant, and inorganic carbon source by wet method to form a raw material solution; S2. Preparation of precursor powder: drying the raw material solution to achieve solid-liquid separation to obtain dry precursor powder; S3, high temperature calcination: calcine the above precursor powder in a protective atmosphere to form a highly crystalline Na 2+2x Fe 2-x (SO4)3 / C materials; S4, Precursor slurry mixing: Dissolve the sodium supplement compound in the organic reagent and add the highly crystalline Na 2+2x Fe 2-x (SO4)3 / C material, forming a precursor slurry; S5, drying and separation: drying the precursor slurry to remove the organic reagent to obtain the pre-sodiumized Na 2+2x Fe 2-x (SO4)3 / C composites; In Na 2+2x Fe 2-x In (SO4)3, 0≤x0.

5.

2. The method for preparing the pre-sodiumized sodium ferric sulfate positive electrode material for sodium ion batteries according to claim 1, wherein: In step S4, the amount of sodium supplementing compound added is 1.5-5wt% of the weight of the sodium ferric sulfate material.

3. The method for preparing the pre-sodiumized sodium ferric sulfate positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step S4, the sodium supplement compound is one or more of sodium oxalate, sodium carbonate, sodium bicarbonate, sodium oxide, and sodium peroxide.

4. The method for preparing the pre-sodiumized sodium ferric sulfate positive electrode material for sodium ion batteries according to claim 1, wherein: In step S4, the organic reagent is one or more of ethanol, acetone, acetonitrile, ether, and benzene.

5. The method for preparing the pre-sodiumized sodium ferric sulfate positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step S3, the calcination temperature is 320-430°C, and the time is >0.01H.

6. The method for preparing the pre-sodiumized sodium ferric sulfate positive electrode material for sodium ion batteries according to claim 1, characterized in that: In steps S2 and S5, the drying method is one or more of flash drying, spray drying, vacuum drying, freeze drying, and air drying.

7. The method for preparing the pre-sodiumized sodium ferric sulfate positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step S3, the protective atmosphere is one or more of nitrogen, argon, nitrogen-hydrogen, and argon-hydrogen.

8. The method for preparing the pre-sodiumized sodium ferric sulfate positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step S1, the antioxidant is one or more of ascorbic acid and its derivatives, phytic acid and its derivatives, butylated hydroxymethoxybenzene, tert-butylhydroquinone, butylated hydroxytoluene, and ethoxyquinoline.

9. The method for preparing the pre-sodiumized sodium ferric sulfate positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step S1 , the inorganic carbon is one or more of carbon black and its derivatives, graphene and its derivatives, carbon nanotubes and its derivatives, and carbon fibers and their derivatives.

10. The method for preparing the pre-sodiumized sodium ferric sulfate positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step S1, the iron source is one or more of ferrous sulfate, ferric sulfate, iron powder, ferrous oxide, ferric oxide, ferric hydroxide, ferric oxide, ferric acetate; the sulfur source is one or more of sulfuric acid, ferrous sulfate, ammonium sulfate, and sodium sulfate; the sodium source is one or more of sodium formate, sodium acetate, sodium sulfate, sodium nitrate, sodium hydroxide, sodium carbonate, and sodium bicarbonate.